Peptidrezeptor-Radionuklidtherapie Somatostatinrezeptor- exprimierender Tumore - Poeppel, T. D.; Boy, C.; Bockisch, A.; Kotzerke, J.; Buchmann, I.; Ezziddin, S.; Scheidhauer, K.; Krause, B. J.; Schmidt, D.; Amthauer, H.; Rösch, F.; Nagarajah, J.; Führer, D.; Lahner, H.; Pöpperl, G.; Hörsch, D.; Walter, M. A.; Baum, R. P. (Nuklearmedizin - NuclearMedicine, 2015)
Diese Handlungsempfehlung soll eine Grundlage für die Qualitätssicherung der Peptid - rezeptor-Radionuklidtherapie (PRRT) von Patienten mit Somatostatinrezeptor-exprimierenden Tumoren schaffen, die zurzeit in Deutschland bei fehlenden gleichwertigen oder besseren Therapiealternativen im Rahmen eines individuellen Heilversuches erfolgt. Sie wurde interdisziplinär erarbeitet und enthält neben Definition, allgemeiner Zielsetzung und klinischen Hintergrundinformationen Angaben zu Indikationen und Kontraindikationen der PRRT. Im Mittelpunkt stehen die Anforderungen, die an das Behandlungszentrum gestellt werden, wie die enge Zusammenarbeit der an der Behandlung beteiligten Fachgebiete. Weiterhin wird spezifiziert, welche Untersuchungsbefunde vor der Therapie vorliegen müssen und wie die PRRT technisch und organisatorisch durchzuführen ist. Nach der Behandlung ist eine langfristige Nachsorge/Kontrolle der therapierten Patienten – u. a. zur Gewinnung onkologischer Qualitätsparameter – unabdingbar. Die gesamte Behandlung einschließlich der Nachsorge muss in enger Abstimmung und Zusammenarbeit der beteiligten Fachdisziplinen erfolgen, wobei in der Regel die Empfehlung zur PRRT durch ein multidisziplinäres Tumorboard erfolgen sollte.This document describes the guideline for peptide receptor radionuclide therapy (PRRT) published by the German Society of Nuclear Medicine (DGN) and accepted by the Association of the Scientific Medical Societies in Germany (AWMF) to be included in the official AWMF Guideline Registry. These recommendations are a prerequisite for the quality management in the treatment of patients with somatostatin receptor expressing tumours using PRRT. They are aimed at guiding nuclear medicine specialists in selecting likely candidates to receive PRRT and to deliver the treatment in a safe and effective manner. The recommendations are based on an interdisciplinary consensus. The document contains background information and definitions and covers the rationale, indications and contraindications for PRRT. Essential topics are the requirements for institutions performing the therapy, e. g. presence of an expert for medical physics, intense cooperation with all colleagues involved in the treatment of a patient, and a certificate of instruction in radiochemical labelling and quality control are required. Furthermore, it is specified which patient data have to be available prior to performance of therapy and how treatment has to be carried out technically. Here, quality control and documentation of labelling are of great importance. After treatment, clinical quality control is mandatory (work-up of therapy data and follow-up of patients). Essential elements of follow-up are specified in detail. The complete treatment inclusive after-care has to be realised in close cooperation with the involved medical disciplines. Generally, the decision for PRRT should be undertaken within the framework of a multidisciplinary tumour board.
Keywords: Neuroendokriner Tumor; NET; NEN; Peptidrezeptor-Radionuklidtherapie; PRRT; Leitlinie; DOTATOC; DOTATATE